2020
DOI: 10.3390/en13246674
|View full text |Cite
|
Sign up to set email alerts
|

Modelling End-User Behavior and Behavioral Change in Smart Grids. An Application of the Model of Frame Selection

Abstract: This paper presents an agent-based model (ABM) for residential end-users, which is part of a larger, interdisciplinary co-simulation framework that helps to investigate the performance of future power distribution grids (i.e., smart grid scenarios). Different modes of governance (strong, soft and self-organization) as well as end-users’ heterogeneous behavior represent key influential factors. Feedback was implemented as a measure to foster grid-beneficial behavior, which encompasses a range of monetary and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…It is a good example of how bottom-up social innovations can shape effective policy actions in terms of the incentive mix. Hoffman, Adelf and Meyer [16] draws similar conclusions, indicating that end-user contributions to collective problem solving are an integral part of non-monetary incentives, which fits into a mixed governance model involving 'soft control' and coordination.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is a good example of how bottom-up social innovations can shape effective policy actions in terms of the incentive mix. Hoffman, Adelf and Meyer [16] draws similar conclusions, indicating that end-user contributions to collective problem solving are an integral part of non-monetary incentives, which fits into a mixed governance model involving 'soft control' and coordination.…”
Section: Discussionmentioning
confidence: 75%
“…Hanke and Lowitzsch highlight that energy transition depend on the participation of all societal groups, hence it is crucial to provide competitive energy prices to energy community members by removing existing obstacles such as high tax and levy burdens or administrative and regulatory complexities [15]. On the other hand, the importance of more prescriptive, non-monetary incentives targeting end-users in the energy system with respect to their engagement in energy matters is highlighted by Hoffman, Adelf and Meyer [16]. By introducing an agent-based model (ABM) for end-users as part of an interdisciplinary simulation system, they indicated that feedback and non-monetary end-user incentives support energy engagement and willingness to cooperate.…”
Section: Introductionmentioning
confidence: 99%